Dialog Komunitas: Menggabungkan Teknologi dan Metodologi Mengajar Inovatif di Sekolah - Ahmad Gani; Taufik Hidayat (Sultan Publsiher, 2024)
Integrating technology into the education process is an important step towards the digital age, especially in Jakarta's school environment.